INFORMATION SYSTEM WITH BIOSENSOR AND DATA PROTECTION: DEVELOPMENT OF CONCEPTUAL DIRECTIONS - Klyuchko , Olena (Ukrainian Information Security Research Journal, 2023)
The purpose of this work is detailed analysis of the possibilities of developing specific methods for data protection in information systems, implemented using technical devices - biosensors. They are incorporated into information systems as their elements and they are connected functionally by electrical signals at the output of biosensors; the publication analyzes the specific possibilities of encoding information in such complex system. In process of this work the methods of physical modeling of biosensors as elements of information systems, development of information monitoring system with databases, methods of comparative analysis of characteristics of input and output electrical information signals of biosensor were applied. The concept of biosensors and their properties are considered, including ones in experimental system with registration of output electrical information signals - the property of information signals coding by such biotechnical device, etc. A physical model was developed and some results of this device testing were given. The functions of neuro-like biosensor were observed briefly: receiver of input information signals - filter - analyzer - encoder / decoder. The co-relations between input biosensor information signals (chemical signals) and after their coding at the output (electrical signals) is shown in tabular form. As example, the information system with databases and biosensors was observed; it was constructed for monitoring the presence and identification of harmful chemicals in airport environment. The results of this work can open new opportunities for data protection in information systems.